RAS mutation prevalence among patients with metastatic colorectal cancer: a meta-analysis of real-world data. (September 2017) - Kafatos, George; Niepel, Daniela; Lowe, Kimberley; Jenkins-Anderson, Sophie; Westhead, Hal; Garawin, Tamer; Traugottová, Zuzana; Bilalis, Antonios; Molnar, Edit; Timar, Jozsef; Toth, Erika; Gouvas, Nikolaos; et al.
Aim: A confirmed wild-type RAS tumor status is commonly required for prescribing anti-EGFR treatment for metastatic colorectal cancer. This noninterventional, observational research project estimated RAS mutation prevalence from real-world sources.Materials & methods: Aggregate RAS mutation data were collected from 12 sources in three regions. Each source was analyzed separately; pooled prevalence estimates were then derived from meta-analyses.Results: The pooled RAS mutation prevalence from 4431 tumor samples tested for RAS mutation status was estimated to be 43.6% (95% CI: 38.8–48.5%); ranging from 33.7% (95% CI: 28.4–39.3%) to 54.1% (95% CI: 51.7–56.5%) between sources.Conclusion: The RAS mutation prevalence estimates varied among sources. The reasons for this are not clear and highlight the need for further research.